2023
DOI: 10.2147/ccid.s413853
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of IL-6, PLR and Nail Psoriasis: Screen for the Early Diagnosis of Psoriatic Arthritis

Abstract: Background Early screening or timely prediction of psoriatic arthritis (PsA) are crucial. The study aimed to compare the clinical characteristics, cytokines and inflammation index between plaque psoriasis and PsA to explore their values in the early diagnosis of PsA. Methods This was a case-control study in a single center from January 2021 to February 2023. The differences in clinical characteristics and laboratory examinations between PsA and plaque psoriasis were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…In the same study, it was also observed that there was a positive correlation between the SII and PASI [42]. In a recent study by Liu et al [43], they determined that the PLR and SII values in patients with psoriatic arthritis were higher than in those with plaque psoriasis. In this study, it was determined that the SII decreased after treatment.…”
Section: Discussionmentioning
confidence: 87%
“…In the same study, it was also observed that there was a positive correlation between the SII and PASI [42]. In a recent study by Liu et al [43], they determined that the PLR and SII values in patients with psoriatic arthritis were higher than in those with plaque psoriasis. In this study, it was determined that the SII decreased after treatment.…”
Section: Discussionmentioning
confidence: 87%